Association between peripheral thyroid sensitivity defined by the FT3/FT4 ratio and composite adverse outcome among inpatients with heart failure - Ma, Li; Gou, Manting; Liu, Xingbang; Ding, Li; Ma, Chao (Frontiers in Endocrinology, 2025)
ObjectiveThe free triiodothyronine to free thyroxine (FT3/FT4) ratio is an indicator of peripheral thyroid hormone sensitivity. However, its prognostic value in heart failure (HF) remains unclear.MethodsThis single center prospective cohort study included a total of 402 HF patients. The primary composite outcome was established as either mortality from any cause or HF-related hospitalization within one year. Multivariate Cox regression and Kaplan-Meier analysis assessed associations between the FT3/FT4 ratio and composite endpoint risks, with restricted cubic splines (RCS) exploring potential non-linear relationships.ResultsAmong 402 heart failure patients, 188 (46.8%) experienced the primary composite endpoint. The highest FT3/FT4 tertile (T3) had 38% lower risk than the lowest tertile (T1) (adjusted HR 0.62, 95% CI 0.41-0.94). In the subgroup of patients with subclinical hypothyroidism (SCH), T3 individuals showed an 84% lower risk compared to T1 (adjusted HR 0.16, 95% CI 0.03–0.81). Both the overall cohort and SCH subgroup exhibited an inverse association between FT3/FT4 ratios and adverse outcomes, whereas euthyroid patients demonstrated a U-shaped relationship with composite endpoint hazards (P for nonlinear = 0.004).ConclusionsOur findings suggest that maintaining or restoring higher FT3/FT4 levels may improve clinical outcomes in HF patients. Regular monitoring of this ratio, coupled with tailored interventions based on thyroid functional status, could enhance risk stratification and therapeutic decision-making.